Integrating development in the local cultural context of the KhiLek Sub-District, At Samat District, Roi Et Province. - Thanissro (Thomarach), Phraathikantanakit; Adtasitdho,Dr., PhrakrupaladSommai; Suanmafai, Paitoon (RATANABUTH JOURNAL, 2022)
Parivasakama is classified as Sangkhakamma in Buddhism because it is the process and procedure for monks who have to commit 13 Sanghadisesas, even if any of them are concealed or not. Must strictly adhere to the principles laid down. This is a specific rule of the Sangha because of the sanghadises, even if it is a grievance or a serious offense. In order for the monks to have the practice of being a sex monk to be accepted among the sangha. Create more unity between monks and Buddhists Then bring the results of research to be effective and for the most benefit to Buddhism. research subject “Integrating the Extinction in the Local Cultural Context of the Sangha of Khie Lek Sub-District district may Roi Et Province" has the objective 1.To study the passage of the Theravada Buddhism 2.To study and analyze the current condition of the parinage of the Sangha of Khie Lek Subdistrict district may Roi Et Province 3.To study the integration of intercession in the local cultural context of the Sangha of Khie Lek Sub-district district may Roi Et Province This research is a quality research. The results of the research were as follows: 1. The practice of the Theravada Buddhism was found to be one of the Sangha’s activities related to the practice of Buddhist teachings. It is the order of the right to come out of the sanghadisses. It is the routine of the monks. Article 1 of the 13 observances for the purity of those who practice the rituals. The secularization of the temple is an ongoing arrangement with the aim of giving the monks the opportunity to purify their precepts. It is a continuation of the life of Buddhism. and giving Buddhists an opportunity to make merit with the monks by giving alms Maintain precepts and practice meditation district may Roi Et Province found that monks and people of the community It is regarded as an important part to be involved in the development of the community’s mind as a spiritual leader. The community must help preserve the tradition of the month Ai for newly ordained monks. have studied and learned about the tradition In addition, the burial ceremony is one of the traditions that should be preserved. and preserve